Subacute Sclerosing Panencephalitis, a Measles Complication, in an Internationally Adopted Child - Daniel J. Bonthius; Nicholas Stanek; Charles Grose (Emerging Infectious Diseases, 2000)
A healthy 13-year-old boy who had spent the first 4.5 years of his life in an orphanage in Thailand before adoption by an American couple became ill with subacute sclerosing panencephalitis and died several months later. The boy had most likely contracted wild-type measles in Thailand. Measles complications are a risk in international adoptions.